2021
DOI: 10.3389/fcimb.2021.599924
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Comparison of Epidemic and Non-Epidemic Carbapenem Resistant Klebsiella pneumoniae Strains

Abstract: Over the past few decades, extensively drug resistant (XDR) resistant Klebsiella pneumoniae has become a notable burden to healthcare all over the world. Especially carbapenemase-producing strains are problematic due to their capability to withstand even last resort antibiotics. Some sequence types (STs) of K. pneumoniae are significantly more prevalent in hospital settings in comparison to other equally resistant strains. This provokes the question whether or not there are phenotypic characteristics that may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…KL51 (n = 111/307, 36.1%) and KL64 (n = 104/307, 33.8%) were dominant K-loci types in this study, whereas KL1, KL2, KL5, KL20, KL17, KL51, KL54, KL57 and KL64 are the reported K-loci types from other Indian studies [ 31 ]. KL51 is reported from isolates from the United States, Sweden, United Kingdom [ 34 ], Thailand [ 35 ], and Lebanon [ 36 ]. The phylogenetic tree of the 307 isolates shows the correlation between capsular locus type and sequence type, for example of KL51 with ST231, and of KL64 with ST147 and ST395 ( Supplementary Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…KL51 (n = 111/307, 36.1%) and KL64 (n = 104/307, 33.8%) were dominant K-loci types in this study, whereas KL1, KL2, KL5, KL20, KL17, KL51, KL54, KL57 and KL64 are the reported K-loci types from other Indian studies [ 31 ]. KL51 is reported from isolates from the United States, Sweden, United Kingdom [ 34 ], Thailand [ 35 ], and Lebanon [ 36 ]. The phylogenetic tree of the 307 isolates shows the correlation between capsular locus type and sequence type, for example of KL51 with ST231, and of KL64 with ST147 and ST395 ( Supplementary Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Whole-genome sequences of the samples were used to assign each sample to its correct SG for each of the tested SG resolutions to confirm the ODM data. The E. coli samples EC3-4, EC7-11, and EC18 had been previously sequenced by Fröding et al 34 (assembly accession numbers GCA_013171465.1, GCA_013172225.1, GCA_01317276 5.1, GCA_013174205.1, GCA_013176495.1, GCA_013176595.1, GCA_013176845.1, and GCA_013176885.1) and the K. pneumoniae samples KP2-3, KP7, and KP9 by Koskinen et al 35 (GCA_016056235.1, GCA_015831445.1, GCA_016056215.1, and GCA_015831545.1). These assemblies were all downloaded from GenBank.…”
Section: Methodsmentioning
confidence: 99%
“…These assemblies were all downloaded from GenBank. The samples KP1, KP4-6, and KP8 were sequenced and assembled using the same method as the other K. pneumoniae samples 35 . The remaining samples were sequenced for this study in the following way.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the novel ST (ST-V, gapA1-infB1-mdh-1-pgi8-phoE1-rpoB1-tonB447) was a single-locus variant of ST15 with variation at the tonB gene. KL51 was reported from the United States, Sweden, the United Kingdom ( 33 ), Thailand ( 34 ), and Lebanon ( 35 ). KL112 has been reported from Russia ( 36 ).…”
Section: Discussionmentioning
confidence: 99%